INVESTIGATION OF HEAVY METAL CONTAMINATION IN THE ROADSIDE SOIL AT MORENA DISTRICT IN INDIA - Sharma, Laxmi Kant (International Journal of Research -GRANTHAALAYAH, 2016)
Pollution of natural environment due to release of heavy metals from various sources is a widespread problem throughout the world. This study explains the effect of heavy metal contaminants in Roadside soil of Morena district. Twelve air dried surface soil samples were collected from 50cm – 1m (point A) and twelve from 30m (point B) away from the roadside along a road with a distance of 50 km. Heavy metals were found in both points with highest concentration at 50cm – 1m (point A). Roadside soil is a definite indicator of vehicular pollution from where the high degree of contamination, is expected. The presence of heavy metals like Cu, Cr, Fe, Pb, Zn and Mn in the roadside soil was also considerable.